Distribution of vascular plants in a subalpine-nival gradient of Central Himalaya: current patterns and predictions for future warming climate - Joshi, Laxmi Raj; Ghimire, Suresh Kumar; Salick, Jan; Konchar, Katie M. (Botanica Orientalis: Journal of Plant Science, 2015)
Following the standard method of Global Research Initiative in Alpine Environments (GLORIA), we performed a systematic investigation of vascular plant species distribution along a subalpine to nival gradient in the Central Himalaya. Our study aims to identify the richness and distribution patterns of vascular plant species and biogeographic groups under current climatic conditions and make predictions for their distribution under warmer conditions anticipated by the Intergovernmental Panel on Climate Change (IPCC). Species richness decreased along an increasing elevation gradient. Aspect also influenced richness levels along the study gradient. Biogeographically, a majority of taxa were Himalayan endemics, followed by species with pan-Himalayan distribution. A complete turnover of indicator species along the elevation gradient was observed due to distinct phytoclimates. Twenty three percent of the plant species recorded in the present study showed a narrow elevation amplitude (<1250 masl) and are projected to be most sensitive to rising global surface temperatures. Taxa with restricted geographical distribution and narrow elevation amplitude must adapt through range shift to compensate for expected future increases in temperature. However, limited habitat availability may hinder the ability of high alpine species to migrate upward in elevation. Botanica Orientalis – Journal of Plant Science (2015) 9: 27–39